Mantle heterogeneity in the source region of mid‐ocean ridge basalts along the northern Central Indian Ridge (8°S–17°S). (7th April 2017) - Kim, Jonguk; Pak, Sang‐Joon; Moon, Jai‐Woon; Lee, Sang‐Mook; Oh, Jihye; Stuart, Finlay M.
Abstract: The northern Central Indian Ridge (CIR) between 8°S and 17°S is composed of seven segments whose spreading rates increase southward from ∼35 to ∼40 mm/yr. During expeditions of R/V Onnuri to study hydrothermal activity on the northern CIR in 2009–2011, high‐resolution multibeam mapping was conducted and ridge axis basalts were dredged. The major and trace element and Sr‐Nd‐Pb‐He isotopic compositions of basaltic glasses dredged from the spreading axis require three mantle sources: depleted mantle and two distinct enriched mantle sources. The southern segments have Sr, Nd, and Pb that are a mix of depleted mantle and an enriched component as recorded in southern CIR MORB. This enrichment is indistinguishable from Rèunion plume mantle, except for He isotopes. This suggests that the southern segments have incorporated a contribution of the fossil Rèunion plume mantle, as the CIR migrated over hot‐spot‐modified mantle. The low 3 He/ 4 He (7.5–9.2 RA ) of this enriched component may result from radiogenic 4 He ingrowth in the fossil Rèunion mantle component. Basalts from the northern segments have high 206 Pb/ 204 Pb (18.53–19.15) and low 87 Sr/ 86 Sr (0.70286–0.70296) that are distinct from the Rèunion plume but consistent with derivation from mantle with FOZO signature, albeit with 3 He/ 4 He (9.2–11.8 RA ) that are higher than typical. The FOZO‐like enriched mantle cannot be attributed to the track of a nearby mantle plume. Instead, this enrichment may have resulted from recycling oceanic crust, possibly accompanied by small plume activity. Key Points: Examination of origin of E‐MORB far from hot spots in the Central Indian Ridge E‐MORB in southern segment affected by fossil Rèunion mantle component E‐MORBs independent from hot spot in northern segment show FOZO composition